Transcriptome Analysis of Dendrobine Biosynthesis in Trichoderma longibrachiatum MD33 - Jia, Qi; Wang, Lina; Qian, Xu; Jin, Hui; Shu, Fuxing; Sarsaiya, Surendra; Jin, Leilei; Chen, Jishuang (Frontiers in Microbiology, 2022)
Dendrobine is a representative component of Dendrobium nobile, and its pharmacological effects have been extensively studied. Trichoderma longibrachiatum MD33 was isolated from the stem of Dendrobium nobile which can produce dendrobine. In order to understand the effect of Methyl Jasmonate (MeJA) on the production of dendrobine, transcriptome analysis was performed after MeJA treatment in the MD33 and control groups. The dendrobine production of MeJA (20 μmol/L) treatment group was 44.6% higher than that of control. In this study, the RNA sequencing technology was applied, a total of 444 differentially expressed genes (DEGs) in the control and MeJA treatment groups, including 226 up-regulated genes and 218 down-regulated genes. The Kyoto Encyclopedia of Genes and Genomes annotation showed that numbers of DEGs were associated with the putative alkaloid biosynthetic pathway in T Trichoderma longibrachiatum MD33. Several MVA pathway enzyme-coding genes (isopentenyl-diphosphate Delta-isomerase, iphosphomevalonate decarboxylase and farnesyl diphosphate synthase) were found to be differentially expressed, suggesting an active precursor supply for alkaloid biosynthesis after MeJA treatment, in other wise, dendrobine may synthesis through the MVA pathway in MD33. Numerous MeJA-induced P450 family genes, aminotransferase genes and methyltransferase genes were identified, providing several important candidates to further elucidate the dendrobine biosynthetic pathway of T. longibrachiatum MD33. Furthermore, several MeJA-induced transcription factors (TFs) encoding genes were identified, suggesting a complex genetic network affecting the dendrobine in T. longibrachiatum MD33. These findings reveal the regulation mechanism underlying the MeJA-induced accumulation of dendrobine in T. longibrachiatum MD33.